The General Basis of Arbitrator Behavior: An Empirical Analysis of Conventional and Final-Offer Arbitration - Farber, Henry S.; Bazerman, Max H. (Econometrica, 1986)
A general model of arbitrator behavior in conventional and final-offer arbitration is developed that is based on an underlying notion of an appropriate award in a particular case. This appropriate award is defined as a function of the facts of the case independently of the offers of the parties. In conventional arbitration the arbitration award is argued to be a function of both the offers of the parties and the appropriate award. The weight that the arbitrator puts on the appropriate award relative to the offers is hypothesized to be a function of the quality of the offers as measured by the difference between the offers. In final-offer arbitration it is argued that the arbitrator chooses the offer that is closest to the appropriate award. The model is implemented empirically using data gathered from practicing arbitrators regarding their decisions in twenty-five hypothetical cases. The estimates of the general model strongly support the characterizations of arbitrator behavior in the two schemes. In addition, no substantial differences were found in the determination of the appropriate award implicit in conventional arbitration decisions and the determination of the appropriate award implicit in the final-offer decisions.